Allele frequency spectrum of known ankylosing spondylitis associated variants in a Swedish population. (2nd January 2022) - Mathioudaki, A; Nordin, J; Kastbom, A; Söderkvist, P; Eriksson, P; Cedergren, J; Lindblad-Toh, K; Meadows, JRS
Abstract : Objective : The genetic predisposition to ankylosing spondylitis (AS) has been most widely studied in cohorts with European ancestry. However, within Europe, disease prevalence is higher in Sweden. Given this, we aimed to characterize known AS susceptibility variants in a homogeneous Swedish data set, assessing reproducibility and direction of effect. Method : The power to detect association within an existing Swedish targeted sequencing study (381 controls; 310 AS cases) was examined, and a set of published associations (n = 151) was intersected with available genotypes. Association to disease was calculated using logistic regression accounting for population structure, and HLA-B27 status was determined with direct polymerase chain reaction genotyping. Results : The cases were found to be 92.3% HLA-B27 positive, with the data set showing ≥ 80% predictive power to replicate associations, with odds ratios ≥ 1.6 over a range of allele frequencies (0.1–0.7). Thirty-four markers, representing 23 gene loci, were available for investigation. The replicated variants tagged MICA and IL23R loci (p < 1.47 × 10 −3 ), with variable direction of effect noted for gene loci IL1R1 and MST1 . Conclusion : The Swedish data set successfully replicated both major histocompatibility complex (MHC) and non-MHC loci, and revealed a different replication pattern compared to discovery data sets. This was possibly due to population demographics, including HLA-B27 frequency and measured comorbidities.